Design and development of Shake-Charged torchlight - Lee, Ing Choon (School of Materials Engineering, University Malaysia Perlis, 2010)
A prototype of Shake-Charged Torchlight has been designed and developed in this Final Year Project. Shake-Charged Torchlight is an additional mechanism which allows to be self-charged by shaking movement. This torchlight contains a powerful magnet that is designed to slide back and forth freely in the body of the body of the torchlight and tightly wrapped coil of wire that surrounds the place where the magnet moves. When the torchlight is shaken, the movement of the magnet back and forth in the coil of wire produces electricity that alternates back and forth in polarity. To make it useful for the flashlight, this electricity travels through diodes that change the electricity to always be a consistent polarity like a battery would have. This electricity is then stored in the capacitor where it can be used like in the rechargeable battery.